Early anastomotic leaks after esophagectomy for cancer - Dural, Koray; Yildirim, Erkan; Han, Serdar; Kaplan, Tevfik; Sakinci, Unal (Contemporary Oncology/Współczesna Onkologia, 2004)
Objectives. We have retrospectively evaluated the outcomes of both the cervical and the thoracic anastomoses in esophageal carcinomas in the early postoperative period. Methods. We performed 75 esophagectomy operations in a group of 93 patients diagnosed as esophageal carcinoma between 1990 and 2002. We compared two patient groups (49 thoracic anastomoses, 26 cervical anastomoses) who underwent esophagectomy for esophageal carcinoma according to early complications especially emphasizing anastomotic leaks. Results. Anastomotic leak was seen in 8 patients in the thoracic anastomosis group whereas in 6 patients in the cervical anastomosis group (p=0.0827). The anastomotic leak ratios were 14% in stage II, 17% in stage III and 38% in stage IV (p<0.05). No patient died during the operation. Eight patients (11%) died in the early postoperative period, all of them in the thoracic anastomoses group. According to the distance from the surgical resection margin, the anastomotic leak ratios were 22% in the <3cm group whereas in the ≥3cm group 16% (p=0.9279). The mortality rate was 100% in the thoracic anastomosis group, but in contrast no mortality was noted in cervical anastomosis group. Conclusions. Total esophagectomy and cervical anastomosis is a safe surgical procedure. If anastomotic leaks occur in the thoracic anastomoses the mortality is very high whereas in cervical anastomoses leaks can be easily treated with rewarding results.